Point-contact-spectroscopy evidence of quasi-particle interactions in RNi2B2C(R=Ho, Y): Электpонные свойства металлов и сплавов - Jansen, I. K.; Wyder, V. V.; Yanson, A. G. M.; Fisun, P.; Canfield, P. C.; Cho, B. K.; Tomy, C. V.; Paul, D. McK. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The point-contact (PC) d2V/dI2-spectra of HoNi2B2C and YNi2B2C reveal structure at applied voltages corresponding to the phonon frequencies. At about 4 meV a maximum is observed in the phonon density of states by analogy to the soft-phonon structure in neutron scattering experiments for LuNi2B2C [ P. Dervenagas et al., Phys. Rev. B52, R9839 (1995)] and YNi2B2C [H. Kawano et al., Czech.J. Phys. 46, S2-825 (1996), Phys. Rev. Lett. 77, 4628 (1996)]. In the Ho compound the low-energy phonon peak is suppressed by an applied magnetic field in an anisotropic way, pointing to an interaction between the phonons and the magnetic systems. Surprisingly, in the nonmagnetic Y compound the 4-meV peak is also suppressed by a magnetic field. In the Ho-compound contacts which show the &quotquasi-thermal&quot behavior, the detailed magnetic-field and temperature dependences of the PC spectra suggest that the magnetic order is destroyed due to the coupled phonon-magnon subsystem which is driven out of equilibrium by electrons that pass through the contact, by analogy with the nonequilibrium phonon-induced destruction of the superconducting state in point contacts [I. K. Yanson et al., JETP Lett. 45, 543 (1987)]. The PC electron-phonon interaction (EPI) spectral functions are reconstructed and the estimates for the lambda -parameter yield values of the order of 0.1. Comparison with PC EPI spectra of nonsuperconducting and nonmagnetic LaNi2B2C [I. K. Yanson et al., Phys. Rev. Lett. 78, 935 (1997)], as well as the comparative study of PC EPI and Andreev-reflection spectra for various contacts with superconducting Ho and Y compounds suggest that the low-energy part of the electron-quasi-particle interaction spectral function is responsible for the Cooper pairing in these materials.